Data forwarding incentive mechanism based on auction model in mobile social network - Hao LIU; Zhi-gang CHEN; Lian-ming ZHANG (Tongxin xuebao)
Abstract:A data forwarding incentive mechanism based on auction model in mobile social network was proposed.In this incentive mechanism,the first-price sealed auction mode was extended,the transaction mode of virtual currency payment was adopted,and the procedure of data forwarding between nodes was abstracted into the auction transaction model.Based on the node's resource state,the virtual currency and the data property,the evaluation function of data forwarding transaction was given,and then the node gives the corresponding price according to the evaluation function and game strategy.Through the game analysis,the Nash equilibrium solution of AMIM was found,and the lowest bidder,of which the bid price was lower than the evaluation of data forwarding request node would been selected as the service provider for this data forwarding.In this incentive mechanism,the rational mobile nodes were enforced to voluntarily participate in data forwarding cooperation to maximize their own interests.The simulation experiment shows that AMIM mechanism can effectively reduce the energy consumption and improve the success rate and efficiency of data forwarding in the whole network system.